Evaluation of luciferase reporter bacteriophage A511::luxAB for detection of Listeria monocytogenes in contaminated foods. - Loessner, M J (1997)
A511::luxAB is a recombinant derivative of a broad-host-range bacteriophage specific for the genus Listeria, transducing bacterial bioluminescence into infected cells. In this study, we have evaluated its use for rapid and easy testing of contaminated foods and environmental samples for the presence of viable Listeria cells, in comparison to the standard plating procedure. With a short preenrichment step of 20 h, the system was capable of detecting very low initial contamination rates in several foods artificially contaminated with Listeria monocytogenes Scott A cells. In ricotta cheese, chocolate pudding, and cabbage, less than one cell per g of food could be clearly identified by comparing the light emission of phage-infected samples to that of controls without lux phage. In foods having a large and complex microbial background flora, such as minced meat and soft cheese, at least 10 cells per g were necessary to produce a positive bioluminescence signal. Of 348 potentially contaminated natural food and environmental samples, 55 were found to be Listeria positive by the lux phage method. The standard plating procedure detected 57 positive samples. Some differences were observed with respect to the individual samples, i.e., the lux phage procedure detected more positive samples among the dairy products and environmental samples, whereas the plating procedure revealed more contaminated meat and poultry samples. Overall, both methods performed similarly, i.e., were equally sensitive. However, the minimum time required for detection of Listeria with the luciferase phage assay was 24 h, which is much shorter than the 4 days needed by the standard plating method. Furthermore, a most probable number technique with three parallels, based on the use of A511::luxAB for differentiation of positive and negative tubes, is described. The method enables rapid enumeration of low levels of Listeria cells in several foods tested, against the background of a competing microflora.